2013
DOI: 10.4335/11.3.799-810(2013)
|View full text |Cite
|
Sign up to set email alerts
|

Parents Satisfaction with Preschool Education Service, As Determinant of Service Improvement

Abstract: The objective of this paper is to analyze the overall users’ satisfaction with preschool institutions, and the correlation between different socio-economic characteristics of the respondents and their satisfaction with the obtained services. A survey was conducted in seven towns and municipalities in the Province of Vojvodina in Serbia, including 7798 parents of children using preschool services. The research instrument was a questionnaire composed based on similar surveys of user satisfaction. Multiple regres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…In addition, high-income parents mostly indicate the developmental aspects of the preschool education institution (Grogan, 2012). It has been shown that parents living in urban areas and with high economic and social status have higher expectations from preschool education and their ratings are lower with satisfaction from the service provided (Zivotic et al, 2013). It can be said that the finding of the relationship between the income status of the parents and their expectations from the institution overlaps with the literature.…”
Section: Discussionmentioning
confidence: 92%
“…In addition, high-income parents mostly indicate the developmental aspects of the preschool education institution (Grogan, 2012). It has been shown that parents living in urban areas and with high economic and social status have higher expectations from preschool education and their ratings are lower with satisfaction from the service provided (Zivotic et al, 2013). It can be said that the finding of the relationship between the income status of the parents and their expectations from the institution overlaps with the literature.…”
Section: Discussionmentioning
confidence: 92%
“…Some of these studies are : (Munther,2008 ;Prayukvong &Sornprasith. et al, 2018;Zivotic& Mikanovic, 2013) . As well as the results of studies showed a difference in the impact of some variables on the level of satisfaction of parents about the service quality , the most important of these variables are the variable of educational qualification and economic situation.…”
Section: Literature Review/ Previous Studiesmentioning
confidence: 98%
“…The results showed that there were statistical differences in the sub-measures when comparing the parents' choices attributed to the variable of the age group of the children. (Zivotic & Mikanovic, 2013): This study aimed at analyzing the parents' satisfaction with the services provided by pre-school institutions. The study sample consisted of ( 7798 ) parents, and the study used a questionnaire consisting of items to measure the satisfaction of beneficiaries .The results of the study showed that the parents with higher educational qualifications were less satisfied with the preschool education services .The results also showed that the parents living in urban areas and with higher economic and social status and contributing in paying the preschool expenses had higher expectations of preschool education and their ratings come with a lower level of satisfaction with the service provided .…”
Section: Literature Review/ Previous Studiesmentioning
confidence: 99%